Smart natural technology & maintenance of sustainable aquatic environment: A study during lockdown - Sucharita Bhattacharyya; Anwesh Bhowmick (Science Talks)
Natural climatic changes and human activities affect environmental balance influencing various global ecosystems including the aquatic one. Here the Gangetic ecosystem of India with Dolphin is focused. The Ganges is India's longest river and its lifeline contributing immensely to the country's overall GDP. Again, it is home to many animals including the Dolphin, recognized to be a reliable health indicator with its hydrodynamic body system which works efficiently by the smart natural technique of echolocation and desquamation. However, industrial effluents, agricultural runoffs, discharge of untreated wastewater along with sedimentation produce gross negative effects on the Gangetic environment. These directly pollute the river, disrupt its regular flow, and obstruct the normal activities of the Dolphin, thus destroying its habitat which ultimately reduces the population and affects the river's bio-diversity balance. Country-wide lockdown during the COVID-19 Pandemic temporarily stops all human interventions. The net outcome is the rejuvenation of the water quality confirmed by the reappearance of the Dolphins after several years along its various stretches. So how the identified steps should be practiced to maintain the Gangetic ecosystem, while maintaining the country's economic growth, has been considered as the greatest challenge here.